أنواع أخطاء القراءة عند التلاميذ الذين يعانون صعوبة تعلم القراءة - سالمي, يسرى; فدول, سارة (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة: تهدف الدراسة إلى التعرف على أنواع أخطاء القراءة عند التلاميذ الذين يعانون صعوبة تعلم القراءة. وقد تمحورت الدراسة حول التساؤل الآتي: -ما هي الأخطاء القرائية الموجودة تلاميذ السنة الثالثة عسيري القراءة؟ فرضية الدراسة: - توجد أخطاء قرائية لدى تلاميذ السنة الثالثة عسيري القراءة . وقد اعتمدت على المنهج الوصفي باعتباره أكثر المناهج ملائمة لموضوع البحث، إذ تكونت عينة الدراسة من (30) تلميذ من إبتدائية بالرابح إسماعيل، وقد تم اختيارهم بطريقة عشوائية بسيطة، وللإجابة على تساؤلات الدراسة فقد طبق إسماعيل العيس (2015) ولمعرفة صحة الفرضيات من عدمها تم استخدام النسبة المئوية للكشف أنواع أخطاء القراءة عند التلاميذ الذين يعانون صعوبة تعلم القراءة لدى تلاميذ السنة الثالثة إبتدائي. وقد تم التوصل الى النتائج التالية: توجد علاقة ارتباطية دالة إحصائيا بين صعوبة تعلم القراءة وكمية أخطاء القراءة المرتكبة من طرف التلميذ، والتي تشكل بدورها عبئا معرفيا على ذوي الصعوبات في القراءة Study summary: The study aims to identify the types of reading errors among students who have difficulty learning to read. The study focused on the following questions: Are there statistically significant differences in reading errors among third year primary school students according to the gender variable? - Are there statistically significant differences in the difficulty of recognizing and reading words among third-year primary school students according to the gender variable? Study hypotheses: - There are statistically significant differences in reading errors among third-year primary school students, according to the gender variable. - There are statistically significant differences in the difficulty of recognizing and reading words among third-year primary school students, according to the gender variable. It relied on the descriptive approach as it is the most suitable method for the subject of the research, as the study sample consisted of (30) students from primary school in El-Rabeh Ismail, and they were chosen in a simple random way. Using the percentage to detect the types of reading errors among students who have difficulty learning to read in the third year of primary school. The following results have been reached: There is a statistically significant correlation between the difficulty of learning to read and the number of reading errors committed by the student, which in turn constitutes a cognitive burden on people with reading difficulties. After discussing the results in the light of the findings of the study, suggesting participation and involvement in various associations that contribute to building perceptions of their future professional prospects and developing counseling and preventive programs to reduce anxiety based on promoting positive thinking through specialists and experts.
دراسة ميدانية في إبتدائية بالرابح إسماعيل بالمغير
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: صعوبات القراءة، difficultés de lecture, reading difficulties; مهارات القراءة، compétences en lecture, reading skills